PENGARUH PENGGUNAAN COOKING VIDEO DI YOUTUBE TERHADAP MOTIVASI BELAJAR SISWA KELAS XI TATA BOGA PADA MATA PELAJARAN PASTRY DAN BAKERY SMK NEGRI 6 BUNGO - Azzahra, Zabila; Prahagia, Yelvia; wicaksono, nurzahra fathiyanabila (Jurnal Pendidikan Vokasi dan Seni, 2025)
This study aims to analyze the effect of using cooking videos on YouTube on the learning motivation of class XI Culinary Arts students in Pastry and Bakery subjects at SMK Negeri 6 Bungo. In addition, the study also wants to determine the factors that influence the effectiveness of video media and the relationship between video use and student learning motivation. The method used is a quantitative approach with a survey design. The research sample consisted of 31 students selected by purposive sampling. The questionnaire instrument was tested for validity and reliability using SPSS 25, with a Cronbach's Alpha value of 0.916 for the video use variable and 0.894 for learning motivation, indicating high reliability. The results of the analysis showed that the data were normally distributed and simple linear regression produced the equation Y = 12.804 + 0.888 X. This means that the more intense the use of cooking videos, the higher the students' learning motivation. The hypothesis test confirmed these findings, with a t-value of 9.593 and a p-value of 0.000 (<0.05), indicating a significant effect. Furthermore, the correlation between video use and learning motivation was very strong, with a Pearson correlation value of 0.872. Overall, this study concluded that using cooking videos on YouTube significantly increased students' learning motivation. Keywords : youtube, cooking video, learning motivation, culinary art, pastry and bakery